PRESERVING TRADITIONAL KNOWLEDGE IN THE DIGITAL ERA: CHALLENGES AND STRATEGIES - Septika Laily Anti; Ifan Awanda (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
Traditional Knowledge (TK) is a cultural heritage that plays a crucial role in the identity of Indigenous communities, biodiversity conservation, and environmental sustainability. However, the digital era poses significant challenges to TK preservation, including the loss of Indigenous languages, lack of intellectual property protections, technological gaps, and the risks of commercialization and misappropriation. This study reviews the primary challenges in safeguarding TK and explores strategies to ensure its sustainability. A systematic literature review method was employed, drawing from various academic and policy sources related to TK. Findings indicate that ethical digitization, legal reforms, decentralized technologies such as blockchain, and cross-sector collaborations significantly contribute to TK protection. Successful initiatives like India's Traditional Knowledge Digital Library (TKDL) and Canada’s blockchain-based TK documentation illustrate that preservation efforts are most effective when communities are actively involved as knowledge custodians. By implementing community-driven and sustainable technological approaches, TK can be transmitted to future generations while maintaining its original cultural significance and context.